Micro Photo Detector Fabricated of Ferroelectric-Metal Heterostructure - Zomorrodian, A (Japanese journal of applied physics. Part 1, Regular papers & short notes, 2005)
The anomalous photovoltaic effect (APE) in ferroelectric thin films has been utilized for the development of an optical micro-detector active in the visible range (from 350 to 800 nm). La-doped Pb(Zr,Ti)O(3) (PLZT) ferroelectric films epitaxially grown on Pt(001)/Mg(001) substrate were fabricated into micro-detector arrays and characterized as to their optical response. The Au/PLZT/Pt/MgO device was self-polarized in the as-deposited form with the polarization vector perpendicular to film surface. The heterostructure photovoltage response ranged from 100 to 200 mV, and the photocurrent was ~30 nA/cm(2) for devices of ~250 μm diameter under illumination of 100 mW/cm(2) at wavelengths from 400 to 580 nm. Such micro-detectors can be used for optical sensors in MEMS devices as well as for electrical stimulators of biological cells